2023
DOI: 10.1503/cmaj.230045
|View full text |Cite
|
Sign up to set email alerts
|

Acute care related to cannabis use during pregnancy after the legalization of nonmedical cannabis in Ontario

Abstract: Background: Cannabis use during pregnancy is increasing, but the contribution of cannabis legalization to these trends is unclear. We sought to determine whether health service utilization related to cannabis use during pregnancy increased after the legalization of nonmedical cannabis in October 2018 in Ontario, Canada. Methods: In this population-based, repeated cross-sectional study, we evaluated changes in the number of pregnant people who received acute care (emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(46 reference statements)
0
1
2
Order By: Relevance
“…The results of this study did not support our hypothesis that cannabinoid use would increase during the post-legalization period; rather, there was a statistically significant decrease in observed utilization. This is inconsistent with other studies which have found increased rates of cannabinoid use in both the general population ( 15 , 47 , 48 ) and specifically during the pre-conception, prenatal, and post-partum time periods ( 16 , 17 ) following the legalization period in other states. This trend of increased use of cannabinoid products during pregnancy has also been shown in other countries including Canada ( 17 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of this study did not support our hypothesis that cannabinoid use would increase during the post-legalization period; rather, there was a statistically significant decrease in observed utilization. This is inconsistent with other studies which have found increased rates of cannabinoid use in both the general population ( 15 , 47 , 48 ) and specifically during the pre-conception, prenatal, and post-partum time periods ( 16 , 17 ) following the legalization period in other states. This trend of increased use of cannabinoid products during pregnancy has also been shown in other countries including Canada ( 17 ).…”
Section: Discussioncontrasting
confidence: 99%
“…This is inconsistent with other studies which have found increased rates of cannabinoid use in both the general population ( 15 , 47 , 48 ) and specifically during the pre-conception, prenatal, and post-partum time periods ( 16 , 17 ) following the legalization period in other states. This trend of increased use of cannabinoid products during pregnancy has also been shown in other countries including Canada ( 17 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] An increase in cannabis-induced psychosis in young adults (older than 19 yr) has been reported in some 13 but not all studies, 14 and the number of pregnant women needing hospital care for cannabis-related problems has doubled. 15 Additionally, studies have shown an increase in injured drivers who used cannabis. 16 These findings primarily reflect periods with immature cannabis markets and coincide with the COVID-19 pandemic, complicating the assessment of Bill C-45's impact.…”
Section: Early Health Indicators Of Cannabis Policy Changesmentioning
confidence: 99%